Iron-silicon-aluminum magnetic powder core and preparation method and application thereof
By using double-layer coating technology on the ferrosilicon aluminum magnetic powder core, boric acid and metal ions form a stable mesh-like borate, and on the basis of this, an inorganic gel composed of nano-difference ceramic powder and concave and concave and concave and convex rod soil is used for the formation of a stable mesh-like borate salt. Further cladding solves the problems of poor DC superposition capability and high loss in large current scenarios, achieving efficient resistivity and thermal stability, and is suitable for small, high-frequency, and high-current electronic products.
Patent Information
- Application Number
- CN202311038769.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-21
AI Technical Summary
The existing ferrosilicon aluminum magnetic powder core has poor DC superposition capability and high losses in large current scenarios, making it difficult to meet the needs of small, high-frequency, and high-current electronic products.
Using double-layer coating technology, Mg2+, Sr2+ or Y3+ ions are first introduced into the boric acid insulating liquid to form a stable network structure borate, and then an inorganic gel pair composed of nano-die ceramic powder and concave and concave rod soil is used on the basis. The powder is further coated to form a dense and uniform nanoceramic-concave and convex rod insulating layer.
The resistivity and thermal stability of the magnetic powder core are significantly improved, power loss is reduced, and DC superposition performance is improved, so that the magnetic powder core has good performance under high temperature annealing conditions of 800℃.
Smart Images

Figure BDA0004399949570000121 
Figure BDA0004399949570000131
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic materials and relates to a sendust magnetic powder core and a preparation method and application thereof. Background Art
[0002] With the development of electronic power technology, it is an inevitable trend for electronic devices to develop in the direction of miniaturization, high frequency and high current. In the future, higher requirements will be placed on the performance indicators of soft magnetic materials. Among soft magnetic materials, Sendust magnetic powder core has a higher Bs, which can achieve higher inductance at the same volume. At the same time, its own advantages such as low loss, low cost, and good temperature and frequency characteristics make Sendust magnetic powder core widely used in switching power supply transformer cores, power correctors, high-frequency power filters, uninterruptible power supplies, and energy storage filter inductors. However, the DC superposition capability of the inductor prepared by Sendust magnetic powder core is poor, which affects its use in high current scenarios. Therefore, improving the defect of poor superposition of Sendust magnetic powder core and further reducing its loss are still hot spots in research and application.
[0003] In traditional iron silicon aluminum insulation coating, one or several insoluble phosphate phosphating films are formed on the surface of the particles through phosphoric acid treatment. Although phosphoric acid can provide excellent surface resistivity and heat resistance, the volatility of phosphoric acid during the annealing heat treatment of the coating will cause the adhesion of the insulating coating to decrease. On the other hand, most companies currently use organic binders for magnetic powder core binders, such as phenolic resin, silicone resin, etc. Organic binders have good bonding effects, but the residual carbon in the magnetic powder core causes the magnetic loss of the magnetic powder core to increase.
[0004] CN110246675A discloses a high saturation magnetic flux density, low loss soft magnetic composite material and its preparation method. The patent adopts three layers of insulation coating: the first layer is coated with phosphoric acid solution to form a phosphate insulation layer; the second layer is coated with a coupling agent to form an organic insulation layer; the third layer is coated with nano powder to form an inorganic insulation layer.
[0005] CN105931790A discloses a sendust magnetic powder core and a preparation method thereof. Sendust powder and iron silicon powder are screened with a specific mesh size, and then the screened powders are passivated with phosphoric acid, and then mixed in different proportions, which greatly reduces the loss of the obtained magnetic core and improves the DC bias capability. However, it only uses phosphoric acid for passivation, which cannot avoid the problem of reduced resistivity caused by the decomposition of the phosphoric acid passivation layer at high temperature.
[0006] CN 112289534 A discloses a sendust magnetic powder core and its preparation method and use. The magnetic powder core comprises sendust powder, a first coating layer and a second coating layer, wherein the first coating layer is coated on the surface of the sendust powder, and the second coating layer is coated on the surface of the first coating layer, wherein the first coating layer is a metal oxide and the second coating layer is a resin material. The phosphate in the insulating layer has poor thermal stability, which is not conducive to further improving the resistivity to reduce eddy current loss.
[0007] The soft magnetic material obtained by the above scheme has the problems of low magnetic permeability, high resistivity, poor stability or serious power loss, and cannot be well adapted to small, high-frequency, and high-current electronic products. Summary of the invention
[0008] The object of the present invention is to provide a sendust magnetic powder core and a preparation method and application thereof. The sendust magnetic powder prepared by the method of the present invention has a uniform insulation layer, high magnetic permeability, low power loss, high strength after heat treatment, good comprehensive performance of the product, and relatively low cost.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a sendust magnetic powder core, the preparation method comprising the following steps:
[0011] (1) Pre-annealing the atomized Sendust soft magnetic alloy powder;
[0012] (2) mixing boric acid, a metal salt and a solvent to obtain a coating liquid, adding the pre-annealed Sendust soft magnetic alloy powder, and stirring to obtain coated Sendust soft magnetic alloy powder;
[0013] (3) mixing the nano-dielectric ceramic powder and attapulgite with a solvent to form a suspension, heating and stirring the suspension to obtain an inorganic gelled insulating coating liquid, and mixing and stirring the coated Sendust soft magnetic alloy powder in step (2) with the inorganic gelled insulating coating liquid to obtain a double-layer coated Sendust soft magnetic alloy powder;
[0014] (4) The double-layer coated Sendust soft magnetic alloy powder is mixed with zinc stearate and pressed, and then subjected to high-temperature annealing to obtain the Sendust magnetic powder core.
[0015] The present invention first introduces Mg into the boric acid insulating liquid 2+ , Sr 2+ or Y 3+Ion solution. Boric acid can effectively improve the heat resistance of the coating, and at the same time form a stable network structure borate during the annealing process of the magnetic core. The metal ion solution introduced at the same time can reduce the crystallization tendency and crystallization speed of the coating, and further improve the heat resistance and resistivity of the coating. In order to further reduce the loss of the magnetic core and improve its resistivity, the powder is further coated with an inorganic gel composed of nano-dielectric ceramic powder and attapulgite binder on the basis of the first coating. The coating layer of nano-ceramic has the advantages of high heat resistance temperature, high resistivity and low price. The heavy coating can coat a dense and uniform nano-ceramic-attapulgite insulation layer on the surface of the soft magnetic powder, which can significantly improve the resistivity of the coating layer, so that the obtained composite material has both good bonding strength and good thermal stability, and can be annealed at 800°C to further reduce the core loss.
[0016] Preferably, the mass fraction of silicon in the Sendust aluminum soft magnetic alloy powder in step (1) is 8.5-10.5%, for example: 8.5%, 9%, 9.5%, 10% or 10.5%, etc.
[0017] Preferably, the mass fraction of aluminum is 4.5-6.5%, for example, 4.5%, 5%, 5.5%, 6% or 6.5%.
[0018] Preferably, the mass fraction of the iron is 83-87%, for example, 83%, 84%, 85%, 86% or 87%.
[0019] Preferably, the Sendust soft magnetic alloy powder in step (1) is sieved through a 120-mesh sieve before pre-annealing.
[0020] Preferably, the sendust soft magnetic alloy powder is sieved into -120 mesh, -120 to -325 mesh and -325 mesh powders after pre-annealing, and the three powders with different particle size distributions are mixed evenly, wherein the -120 mesh powder accounts for 5 to 10% of the total powder mass, the -120 to -325 mesh powder accounts for 45 to 55% of the total powder mass, and the remainder is -325 mesh powder.
[0021] Preferably, the temperature of the pre-annealing treatment in step (1) is 750-850°C, for example, 750°C, 780°C, 800°C, 820°C or 850°C.
[0022] Preferably, the pre-annealing treatment time in step (1) is 1 to 3 hours, for example: 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.
[0023] Preferably, the metal salt in step (2) comprises any one of nitrates, phosphates or carbonates of Mg, Sr or Y, or a combination of at least two thereof.
[0024] Preferably, the solvent in step (2) comprises deionized water.
[0025] Preferably, the mass ratio of the boric acid to the solvent in step (2) is 1:(8-10), for example: 1:8, 1:8.5, 1:9, 1:9.5 or 1:10, etc.
[0026] Preferably, the mass ratio of boric acid to Sendust soft magnetic alloy powder in step (2) is (1-5):100, for example: 1:100, 2:100, 3:100, 4:100 or 5:100, etc.
[0027] Preferably, the mass of the metal ions in the metal salt in step (2) is 20 to 60 ppm of the mass of the Sendust soft magnetic alloy powder, for example, 20 ppm, 30 ppm, 40 ppm, 50 ppm or 60 ppm.
[0028] Preferably, the stirring time in step (2) is 30 to 60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min or 60 min.
[0029] Preferably, the stirring in step (2) is followed by drying.
[0030] Preferably, the drying temperature is 100-120°C, for example, 100°C, 105°C, 110°C, 115°C or 120°C.
[0031] Preferably, the nano-dielectric ceramic powder in step (3) comprises nano-calcium barium zirconate titanate powder and / or nano-barium zirconate titanate powder.
[0032] Preferably, the average particle size of the nano-dielectric ceramic powder in step (3) is 30 to 100 nm, for example, 30 nm, 50 nm, 80 nm, 90 nm or 100 nm.
[0033] Preferably, in step (3), the mass ratio of the nano-medium ceramic powder to attapulgite is (4-8):1, for example: 4:1, 5:1, 6:1, 7:1 or 8:1.
[0034] Preferably, the solid content of the suspension in step (3) is 10-15%, for example: 10%, 11%, 12%, 13%, 14% or 15%, etc.
[0035] Preferably, the temperature of the heating and stirring in step (3) is 50-70°C, for example, 50°C, 55°C, 60°C, 65°C or 70°C.
[0036] Preferably, the heating and stirring time in step (3) is 3 to 5 hours, for example: 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours.
[0037] Preferably, the mass ratio of the total mass of the inorganic particles in the insulating coating liquid in step (3) to the sendust soft magnetic alloy powder is (0.5-6):100, for example: 0.5:100, 1:100, 2:100, 4:100 or 6:100, etc.
[0038] Preferably, the mixing and stirring in step (3) is followed by drying.
[0039] Preferably, the drying temperature is 70-100°C, for example, 70°C, 75°C, 80°C, 90°C or 100°C.
[0040] Preferably, the mass ratio of the zinc stearate to the Sendust soft magnetic alloy powder in step (4) is (0.5-1):100, for example: 0.5:100, 0.6:100, 0.7:100, 0.8:100 or 1:100, etc.
[0041] Preferably, the pressing pressure in step (4) is 800-1200 MPa, for example, 800 MPa, 900 MPa, 1000 MPa, 1100 MPa or 1200 MPa.
[0042] Preferably, the pressing time in step (4) is 10 to 20 seconds, for example, 10 seconds, 12 seconds, 15 seconds, 18 seconds or 20 seconds.
[0043] Preferably, the temperature of the high temperature annealing treatment in step (4) is 700-850°C, for example: 700°C, 750°C, 780°C, 800°C or 850°C.
[0044] Preferably, the high temperature annealing treatment in step (4) is performed for 1 to 4 hours, for example, 1 hour, 1.5 hours, 2 hours, 3 hours or 4 hours.
[0045] In a second aspect, the present invention provides a Sendust magnetic powder core, wherein the Sendust magnetic powder core is made by the method described in the first aspect.
[0046] The surface of the magnetic powder in the sendust magnetic powder core of the present invention is coated with two layers of insulating layers. The two layers of insulating coating can effectively solve the problem of the decomposition of the insulating layer at high temperature resulting in a decrease in resistivity caused by the use of traditional phosphoric acid passivation. At the same time, the introduced metal ions can effectively improve the heat resistance and resistivity of the coating. The nano-dielectric ceramic-attapulgite insulating layer can improve the resistivity of the coating layer while having good bonding strength and thermal stability, and can be annealed at 800°C. The magnetic powder core prepared in the present invention has low power loss and good DC superposition performance. The entire process is simple and the cost is low, which is suitable for mass production.
[0047] In a third aspect, the present invention provides an application of the Sendust magnetic powder core as described in the second aspect, wherein the Sendust magnetic powder core is used for any one of a switching power supply transformer core, a power corrector, a high-frequency power filter, an uninterruptible power supply or an energy storage filter inductor, or a combination of at least two of them.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] (1) The present invention first introduces Mg into the boric acid insulating liquid 2+ , Sr 2+ or Y 3+ Ion solution. Boric acid can effectively improve the heat resistance of the coating, and form a stable network structure of borate during the annealing process of the magnetic core. At the same time, the introduction of metal ion solution can reduce the crystallization tendency and crystallization speed of the coating, further improving the heat resistance and resistivity of the coating.
[0050] (2) On the basis of the first coating, the powder is further coated with an inorganic gel composed of nano-dielectric ceramic powder and attapulgite binder. The coating layer of nano-ceramic has the advantages of high heat resistance, high resistivity and low price. This heavy coating can coat the surface of the soft magnetic powder with a dense and uniform nano-ceramic-attapulgite insulating layer, which can significantly improve the resistivity of the coating layer, so that the obtained composite material has both good bonding strength and good thermal stability, and can be annealed at 800°C to further reduce the core loss.
[0051] (3) The relative magnetic permeability μ' of the sendust magnetic powder core prepared by the method of the present invention can reach above 60.8, and the power loss can reach 453kW / m 3 Below, the DC superposition characteristic is maintained in the range of 60-70% under a magnetic field strength of 100Oe, proving that the Sendust magnetic powder core prepared by this patent has lower power loss and good DC superposition characteristics. DETAILED DESCRIPTION
[0052] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0053] Example 1
[0054] This embodiment provides a sendust magnetic powder core, and the preparation method of the sendust magnetic powder core is as follows:
[0055] (1) Select atomized iron-silicon-aluminum soft magnetic alloy powder (the mass percentage of each component is: Si 8.5%, Al 6%, and the rest is Fe), and sieve it with a 120-mesh screen, take the powder below 120 mesh, and place the sieved iron-silicon-aluminum soft magnetic alloy powder below 120 mesh in a N2 atmosphere for pre-annealing at 810°C for 2 hours to eliminate stress. After pre-annealing, sieve out -120 mesh powder, -120 to -325 mesh powder, and -325 mesh powder. Mix the three powders with different particle size distributions evenly, of which -120 mesh powder accounts for 8% of the total powder mass, -120 to -325 mesh accounts for 50% of the total powder mass, and the remainder is -325 mesh powder;
[0056] (2) placing the pre-treated aerosolized iron-silicon-aluminum alloy soft magnetic powder into a boric acid mixture containing magnesium nitrate and stirring for 60 minutes, wherein the mass of the boric acid is 3wt% of the mass of the soft magnetic alloy powder, the mass ratio of the boric acid to the deionized water is 1:8, and the weight of the added metal ions is 30ppm of the mass of the soft magnetic alloy powder. The stirred powder is placed in a drying oven and dried at a temperature of 100° C. After drying, the soft magnetic alloy powder with a first layer of insulation coating is obtained;
[0057] (3) weighing nano-barium calcium zirconate titanate dielectric ceramic powder with an average particle size of 60 nm and attapulgite in a mass ratio of 6:1, and preparing a suspension with a solid content of 12%, heating to 70°C, and rapidly stirring for 4 hours to obtain an inorganic gelled insulating coating liquid, and fully mixing the soft magnetic alloy powder treated in step (2) and the inorganic gelled insulating coating liquid with an inorganic particle mass of 2.5 wt% of the mass of the soft magnetic alloy powder, and stirring and drying in an environment of 100°C; after drying, obtaining the soft magnetic alloy powder after the second layer of insulation coating;
[0058] (4) The soft magnetic alloy powder after the second layer of insulation coating and 0.8wt% of zinc stearate are mixed evenly to obtain a molding powder. The molding powder is placed in a mold cavity and dry pressed at a pressure of 1000MPa for 10s to obtain a magnetic powder core blank. The magnetic powder core blank is placed in a N2 atmosphere and annealed at 800°C for 2h to obtain the Sendust magnetic powder core.
[0059] Example 2
[0060] This embodiment provides a sendust magnetic powder core, and the preparation method of the sendust magnetic powder core is as follows:
[0061] (1) Select atomized iron-silicon-aluminum soft magnetic alloy powder (the mass percentage of each component is: Si 8.5%, Al 6%, and the rest is Fe), and sieve it with a 120-mesh screen, take the powder below 120 mesh, and place the sieved iron-silicon-aluminum soft magnetic alloy powder below 120 mesh in a N2 atmosphere for pre-annealing at 750°C for 3 hours to eliminate stress. After pre-annealing, sieve out -120 mesh powder, -120 to -325 mesh powder, and -325 mesh powder. Mix the three powders with different particle size distributions evenly, of which -120 mesh powder accounts for 10% of the total powder mass, -120 to -325 mesh accounts for 55% of the total powder mass, and the remainder is -325 mesh powder;
[0062] (2) placing the pre-treated aerosolized iron-silicon-aluminum alloy soft magnetic powder into a boric acid mixture containing strontium nitrate and stirring for 60 minutes, wherein the mass of the boric acid is 1wt% of the mass of the soft magnetic alloy powder, the mass ratio of the boric acid to the deionized water is 1:8, and the weight of the added metal ions is 20ppm of the mass of the soft magnetic alloy powder. The stirred powder is placed in a drying oven and dried at a temperature of 100° C. After drying, the soft magnetic alloy powder with a first layer of insulation coating is obtained;
[0063] (3) weighing nano-barium zirconate titanate powder with an average particle size of 30 nm and attapulgite in a mass ratio of 4:1, and preparing a suspension with a solid content of 10%, heating to 50°C, and rapidly stirring for 3 hours to obtain an inorganic gelled insulating coating liquid, and fully mixing the soft magnetic alloy powder treated in step (2) and the inorganic gelled insulating coating liquid with an inorganic particle mass of 0.5wt% of the mass of the soft magnetic alloy powder, and stirring and drying in an environment of 100°C; after drying, obtaining the soft magnetic alloy powder after the second layer of insulation coating;
[0064] (4) The soft magnetic alloy powder after the second layer of insulation coating and 0.5wt% of zinc stearate are mixed evenly to obtain a molding powder. The molding powder is placed in a mold cavity and dry pressed at a pressure of 800MPa for 20s to obtain a magnetic powder core blank. The magnetic powder core blank is placed in a N2 atmosphere and annealed at 800°C for 2h to obtain the Sendust magnetic powder core.
[0065] Example 3
[0066] This embodiment provides a sendust magnetic powder core, and the preparation method of the sendust magnetic powder core is as follows:
[0067] (1) Select atomized iron-silicon-aluminum soft magnetic alloy powder (the mass percentage of each component is: Si 8.5%, Al 6%, and the rest is Fe), and use a 120-mesh screen to sieve, take the powder below 120 mesh, and place the sieved iron-silicon-aluminum soft magnetic alloy powder below 120 mesh in a N2 atmosphere for pre-annealing at 850°C for 1 hour to eliminate stress. After pre-annealing, sieve out -120 mesh powder, -120 to -325 mesh powder, and -325 mesh powder. Mix the three powders with different particle size distributions evenly, among which -120 mesh powder accounts for 8% of the total powder mass, -120 to -325 mesh accounts for 50% of the total powder mass, and the remainder is -325 mesh powder;
[0068] (2) placing the pre-treated aerosolized iron-silicon-aluminum alloy soft magnetic powder into a boric acid mixture containing yttrium nitrate and stirring for 60 minutes, wherein the mass of the boric acid is 5wt% of the mass of the soft magnetic alloy powder, the mass ratio of the boric acid to the deionized water is 1:10, and the weight of the added metal ions is 100ppm of the mass of the soft magnetic alloy powder. The stirred powder is placed in a drying oven and dried at a temperature of 100°C. After drying, the soft magnetic alloy powder with a first layer of insulation coating is obtained;
[0069] (3) weighing nano-barium calcium zirconate titanate dielectric ceramic powder with an average particle size of 60 nm and attapulgite in a mass ratio of 8:1, and preparing a suspension with a solid content of 12%, heating to 70°C, and rapidly stirring for 4 hours to obtain an inorganic gelled insulating coating liquid, and fully mixing the soft magnetic alloy powder treated in step (2) and the inorganic gelled insulating coating liquid with an inorganic particle mass of 6 wt% of the mass of the soft magnetic alloy powder, and stirring and drying in an environment of 100°C; after drying, obtaining the soft magnetic alloy powder after the second layer of insulation coating;
[0070] (4) The soft magnetic alloy powder after the second layer of insulation coating and 1wt% of zinc stearate are mixed evenly to obtain a molding powder. The molding powder is placed in a mold cavity and dry pressed at a pressure of 1200MPa for 10s to obtain a magnetic powder core blank. The magnetic powder core blank is placed in a N2 atmosphere and annealed at 700°C for 2h to obtain the Sendust magnetic powder core.
[0071] Example 4
[0072] The only difference between this embodiment and embodiment 1 is that no screening is performed after pre-annealing, and other conditions and parameters are exactly the same as those in embodiment 1.
[0073] Example 5
[0074] The only difference between this embodiment and embodiment 1 is that the mass of boric acid is 0.5wt% of the mass of the soft magnetic alloy powder, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0075] Example 6
[0076] The only difference between this embodiment and embodiment 1 is that the mass of boric acid is 6wt% of the mass of the soft magnetic alloy powder, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0077] Example 7
[0078] The only difference between this embodiment and embodiment 1 is that the weight of the metal ions is 10 ppm of the mass of the soft magnetic alloy powder, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0079] Example 8
[0080] The only difference between this embodiment and embodiment 1 is that the weight of the metal ions is 80 ppm of the mass of the soft magnetic alloy powder, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0081] Example 9
[0082] The only difference between this embodiment and embodiment 1 is that the mass of the inorganic particles in the insulating coating liquid is 8wt% of the mass of the soft magnetic alloy powder, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0083] Example 10
[0084] The only difference between this embodiment and embodiment 1 is that the mass of the inorganic particles in the insulating coating liquid is 0.3wt% of the mass of the soft magnetic alloy powder, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0085] Embodiment 11
[0086] The only difference between this embodiment and embodiment 1 is that the mass ratio of the nano-medium ceramic powder to attapulgite is 2:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0087] Example 12
[0088] The only difference between this embodiment and embodiment 1 is that the mass ratio of the nano-medium ceramic powder to attapulgite is 10:1, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0089] Comparative Example 1
[0090] The only difference between this comparative example and Example 1 is that magnesium nitrate is not added in step (2), and the other conditions and parameters are exactly the same as those in Example 1.
[0091] Comparative Example 2
[0092] The only difference between this comparative example and Example 1 is that nano calcium barium zirconate titanate powder is not added in step (3), and the other conditions and parameters are exactly the same as those in Example 1.
[0093] Performance Test:
[0094] (1) Magnetic permeability test: The magnetic cores prepared in the embodiment and the comparative example were tested for the real part μ' of magnetic permeability at 100 kHz using an Agilent E4991A analyzer. The results are shown in Table 1.
[0095] (2) Power loss test: The magnetic cores provided in the embodiment and the comparative example were uniformly wound with 30+5 turns of copper wire with a diameter of 0.4 mm. The test conditions were 100 kHz, 100 mT, and 25° C. The results are shown in Table 1.
[0096] (3) DC superposition characteristics (100Oe) test: The magnetic cores provided in the embodiment and the comparative example are uniformly wound with 30 turns of copper wire with a diameter of 0.4 mm. The test conditions are 100kHz, 1V, and 25°C, and the DC superposition performance of the magnetic ring under a magnetic field strength of 100Oe is calculated. The test results are shown in Table 1:
[0097] Table 1
[0098]
[0099]
[0100] As can be seen from Table 1, from Examples 1-3, the relative magnetic permeability μ' of the sendust magnetic powder core prepared by the method of the present invention can reach above 60.8, and the power loss can reach 453kW / m 3 Below, the DC superposition characteristic is maintained in the range of 60-70% under a magnetic field strength of 100Oe, proving that the Sendust magnetic powder core prepared by this patent has lower power loss and good DC superposition characteristics.
[0101] By comparing Example 1 and Example 4, it can be obtained that in the preparation process of the sendust aluminum magnetic powder core of the present invention, sieving with different mesh sizes after pre-sintering and then mixing can make the particle size matching of the magnetic powder core more reasonable. While obtaining a higher density, adding an appropriate amount of fine powder to reduce the particle size distribution can effectively increase the gap between particles, and the demagnetization factor of the metal powder will also increase, thereby effectively reducing power loss and increasing DC superposition characteristics.
[0102] By comparing Example 1 with Examples 5-6, it can be seen that during the preparation process of the sendustine magnetic powder core of the present invention, the amount of boric acid added will affect its performance. When the mass of boric acid is controlled at 1-5% of the mass of the soft magnetic alloy powder, the performance of the magnetic powder core obtained is better. If the amount of boric acid added is too large, it will lead to an excessive amount of borate, a non-magnetic substance, on the surface of the powder particles, thereby deteriorating the magnetic permeability of the magnetic powder core. If the amount of boric acid added is too small, the thickness of the borate layer on the surface of the powder particles will be uneven or too thin, and it will not be able to effectively provide an insulating coating to increase the resistivity, and thus it will not be able to effectively improve the power loss and DC superposition characteristics of the magnetic powder core.
[0103] By comparing Example 1 with Examples 7-8, it can be seen that during the preparation process of the sendust magnetic powder core of the present invention, the amount of metal ions added will affect its performance. The mass of metal ions in boric acid is controlled at 20-60ppm of the mass of the soft magnetic alloy powder, and the performance of the obtained magnetic powder core is better. If the amount of metal ions added is too large, the crystallization rate of the borate layer will be reduced, and the resistivity of the powder particles will be greatly increased. Although it can effectively reduce power loss and increase DC superposition characteristics, it will sacrifice a certain degree of magnetic permeability. If the amount of metal ions added is too small, the crystallization rate and crystallization tendency of the borate will not be affected enough, and the resistivity of the powder particles cannot be effectively increased, so that the power loss and DC superposition characteristics of the magnetic powder core cannot be fully improved.
[0104] By comparing Example 1 with Examples 9-10, it can be seen that during the preparation process of the sendust magnetic powder core of the present invention, the mass of the inorganic particles in the insulating coating liquid will affect its performance. The mass of the inorganic particles in the insulating coating liquid is controlled at 0.5-6% of the mass of the soft magnetic alloy powder, and the performance of the obtained magnetic powder core is better. If the mass of the inorganic particles in the insulating coating liquid is too large and there is too much non-magnetic material on the surface of the particles, although the power loss and DC superposition characteristics of the magnetic powder core will be improved, the magnetic permeability will be significantly reduced. If the mass of the inorganic particles in the insulating coating liquid is too small, the resistivity cannot be fully increased, and the power loss and DC superposition characteristics of the magnetic powder core cannot be effectively improved.
[0105] By comparing Example 1 with Example 11-12, it can be seen that in the preparation process of the sendust magnetic powder core of the present invention, the mass ratio of the nano-dielectric ceramic powder and the attapulgite will affect its performance. The mass ratio of the nano-dielectric ceramic powder and the attapulgite is controlled at 4 to 8:1, and the performance of the magnetic powder core is better. If the amount of the nano-dielectric ceramic powder added is too large, the mass of the attapulgite as a binder will be relatively small, and then the combination of the nano-dielectric ceramic and the alloy powder particles is not very tight, resulting in a deterioration in power loss and DC superposition characteristics. At the same time, too much nano-dielectric ceramic powder will also cause a certain degree of deterioration in the magnetic permeability of the magnetic powder core. If the amount of the nano-dielectric ceramic powder added is too small, it will not be able to fully improve the resistivity, causing a large degree of deterioration in power loss and DC superposition characteristics.
[0106] By comparing Example 1 with Comparative Example 1, it can be seen that the present invention first introduces Mg into the boric acid insulating liquid 2+ , Sr 2+ or Y 3+Ion solution. Boric acid can effectively improve the heat resistance of the coating, and form a stable network structure of borate during the annealing process of the magnetic core. At the same time, the introduction of metal ion solution can reduce the crystallization tendency and crystallization speed of the coating, further improving the heat resistance and resistivity of the coating.
[0107] By comparing Example 1 and Comparative Example 2, it can be seen that the present invention further coats the powder with an inorganic gel composed of nano-dielectric ceramic powder and attapulgite binder on the basis of the first coating. The coating layer of nano-ceramic has the advantages of high heat resistance, high resistivity and low price. The heavy coating can coat a dense and uniform nano-ceramic-attapulgite insulating layer on the surface of the soft magnetic powder, which can significantly improve the resistivity of the coating layer, so that the obtained composite material has both good bonding strength and good thermal stability, and can be annealed at 800°C to further reduce the core loss.
[0108] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a sendust magnetic powder core, characterized in that: The preparation method comprises the following steps: (1) Pre-annealing the atomized Sendust soft magnetic alloy powder; (2) mixing boric acid, a metal salt and a solvent to obtain a coating liquid, adding the pre-annealed Sendust soft magnetic alloy powder, and stirring to obtain coated Sendust soft magnetic alloy powder; (3) mixing the nano-dielectric ceramic powder and attapulgite with a solvent to form a suspension, heating and stirring the suspension to obtain an inorganic gelled insulating coating liquid, and mixing and stirring the coated Sendust soft magnetic alloy powder in step (2) with the inorganic gelled insulating coating liquid to obtain a double-layer coated Sendust soft magnetic alloy powder; (4) The double-layer coated Sendust soft magnetic alloy powder is mixed with zinc stearate and pressed, and then subjected to high-temperature annealing to obtain the Sendust magnetic powder core.
2. The preparation method according to claim 1, characterized in that The mass fraction of silicon in the Sendust soft magnetic alloy powder of step (1) is 8.5-10.5%; Preferably, the mass fraction of aluminum is 4.5-6.5%; Preferably, the mass fraction of iron is 83-87%.
3. The preparation method according to claim 1 or 2, characterized in that: The Sendust soft magnetic alloy powder in step (1) is sieved through a 120-mesh sieve before pre-annealing; Preferably, the sendust soft magnetic alloy powder is sieved into -120 mesh, -120 to -325 mesh and -325 mesh powders after pre-annealing, and the three powders with different particle size distributions are evenly mixed, wherein the -120 mesh powder accounts for 5 to 10% of the total powder mass, the -120 to -325 mesh powder accounts for 45 to 55% of the total powder mass, and the remainder is the -325 mesh powder; Preferably, the temperature of the pre-annealing treatment in step (1) is 750-850°C; Preferably, the pre-annealing treatment time in step (1) is 1 to 3 hours.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The metal salt in step (2) includes any one of nitrates, phosphates or carbonates of Mg, Sr or Y, or a combination of at least two thereof; Preferably, the solvent in step (2) comprises deionized water; Preferably, the mass ratio of the boric acid to the solvent in step (2) is 1:(8-10); Preferably, the mass ratio of boric acid to Sendust soft magnetic alloy powder in step (2) is (1-5):100; Preferably, the mass of the metal ions in the metal salt in step (2) is 20 to 60 ppm of the mass of the Sendust soft magnetic alloy powder.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The stirring time in step (2) is 30 to 60 minutes; Preferably, the stirring in step (2) is followed by drying; Preferably, the drying temperature is 100-120°C.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The nano dielectric ceramic powder in step (3) includes nano calcium barium zirconate titanate powder and / or nano barium zirconate titanate powder; Preferably, the average particle size of the nano-medium ceramic powder in step (3) is 30 to 100 nm; Preferably, the mass ratio of the nano-medium ceramic powder and attapulgite in step (3) is (4-8):
1.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The solid content of the suspension in step (3) is 10-15%; Preferably, the temperature of the heating and stirring in step (3) is 50-70°C; Preferably, the heating and stirring time in step (3) is 3 to 5 hours; Preferably, the mass ratio of the total mass of the inorganic particles in the insulating coating liquid in step (3) to the sendust soft magnetic alloy powder is (0.5-6):100; Preferably, the mixing and stirring in step (3) is followed by drying; Preferably, the drying temperature is 70-100°C.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The mass ratio of zinc stearate to sendust soft magnetic alloy powder in step (4) is (0.5-1):100; Preferably, the pressing pressure in step (4) is 800-1200 MPa; Preferably, the pressing time in step (4) is 10 to 20 seconds; Preferably, the temperature of the high temperature annealing treatment in step (4) is 700-850°C; Preferably, the high temperature annealing treatment in step (4) is performed for 1 to 4 hours.
9. A Sendust magnetic powder core, characterized in that: The Sendust magnetic powder core is made by the method according to any one of claims 1 to 8.
10. An application of the Sendust magnetic powder core as claimed in claim 9, characterized in that: The Sendust magnetic powder core is used for any one of a switching power supply transformer core, a power corrector, a high-frequency power filter, an uninterruptible power supply or an energy storage filter inductor, or a combination of at least two of them.
Citation Information
Patent Citations
Iron-silicon-aluminum magnetic powder core and preparation method thereof
CN105931790A
Soft magnetic composite material with high saturation magnetic flux density and low loss and preparation method thereof
CN110246675A
Iron-silicon-aluminum magnetic powder core and preparation method and application thereof
CN112289534A